A lentivirus-free inducible CRISPR-Cas9 system for efficient targeting of human genes - Bisht, Kamlesh (Anal Biochem, 2017)
CRISPR-Cas9 is a cutting-edge tool for modifying genomes. The efficacy with which Cas9 recognizes its target has revolutionized the engineering of knockouts. However this efficacy complicates the knocking out of important genes in cultured cells. Unedited cells holding a survival advantage within an edited population can confound the knockout phenotype. Here we develop a HeLa-based system that overcomes this limitation, incorporating several attractive features. First, we use Flp-recombinase to generate clones stably integrated for Cas9 and guide RNAs, eliminating the possibility of unedited cells. Second, Cas9 can be induced uniformly in the clonal cultures using doxycycline to measure the knockout phenotype. Third, two genes can be simultaneously knocked out using this approach. Finally, by not involving lentiviruses, our method is appealing to a broad research audience. Using this methodology we generated an inducible AGO2-knockout cell line showing normal RNA interference in the absence of doxycycline. Upon induction of Cas9, the AGO2 locus was cleaved, the AGO2 protein was depleted, and RNA interference was compromised. In addition to generating inducible knockouts, our technology can be adapted to improve other applications of Cas9, including transcriptional/epigenetic modulation and visualization of cellular DNA loci.